Utilização de resíduos vegetais para a produção de biossurfactantes por fungos isolados de amostras de solo da região amazônica - Sanches, Michele Alves (Universidade Federal do Amazonas, 2016)
Human being has the need to mix water with insoluble substances in their daily and industrial activities. Surfactants derived from petroleum have been used for this purpose, however, they have problems such as their toxicity and biodegradability. Biosurfactants from microbial origin are an alternative to this, on the other hand, its production cost is high due to the substrates that are used in the bioprocesses. In this context, the aim of this study was to investigate the use of wastes as a substrate for the production of biosurfactants by filamentous fungi isolated from soil samples in Amazon region. Bioprocess were conducted with five known fungi isolates producers of biosurfactants in order to investigate which of them would produce in a shorter time. Then, we evaluated the possibility using wastes of peel from tucumã, peach palm, banana, cupuacu and also the post-fry oil as substrate for the bioprocess with the selected isolated. Factors that influence the production of biosurfactant were evaluated by factorial design. As a result, the fungus Fusarium oxysporum 87-2LIVI produced high levels of biosurfactants in three days of bioprocess. Moreover, this specie also showed highlight due to high biosurfactant production using peach palm peel as substract. The pH and yeast extract were the most important factors related to production of biosurfactant by this isolated. Thus, the present study showed isolated of F. oxysporum specie from Amazonian soil is potential producer of surfactants and also Amazon waste, particularly, peel of peach palm has the potential to be used as a bioprocess substrate for production of biosurfactant.